Association of Hand Grip Strength with BMI in Cardiovascular Disease Patients - Khushboo Gulzar, Hamna Waheed, Farooq Islam, Asim Raza, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The strength of one's grip is a good determining factor of their overall muscularity. Grip strength can be utilized in a variety of circumstances to assess and monitor a variety of health-related conditions. Objective: To evaluate the association of hand grip strength with BMI in cardiovascular disease patients. Methodology: An analytical cross sectional study was done on a population basis. A total of 256 patients of cardiovascular diseases were included in this study. Data were collected through purposive sampling technique. A proforma used to get demographic data including name, age, height, weight and occupation. Their BMI was also calculated. Hand grip strength was measured through handheld dynamometer of both hands. Three trials were performed by the patients from both hands. Results: Out of 256 total participants, 133 (52%) were males and 123 (48%) were females. Their mean age was 51.12 (SD = 12.513) and mean BMI was 26.533 (SD = 5.1012). Hand grip strength (HGS) and body mass index (BMI) had a negative and statistically significant association, for dominant hand (pearson’s r = -0.309, p = 0) and for non-dominant hand (pearson’s r = -0.308, p = 0). Mean hand grip strength of dominant hand was 24.677 (SD = 9.0567) and of non-dminant hand was 21.861 (SD = 8.8035). Age and duration of diseases also had a negative and statistically significant association with the hand grip strength of both hands of the patients with p value 0. Conclusion: It was concluded that the BMI had a great impact on HGS. Presence of CVD and the duration of this disease also affect HGS. With increasing age and obesity hand grip strength decreases. Keywords: Body mass index, Hand grip strength, Cardiovascular diseases.